From structural time use to situational rule-breaking: Analysing adolescents’ time use and the person-setting interaction - Chrysoulakis, Alberto P. (European journal of criminology, 2023)
While unsupervised and unstructured socialising with peers is associated with delinquency, less is known about to what extent it fits within adolescents? daily routine activities; that is, their general, structural time use. Furthermore, research informed by the situational action theory shows that unstructured socialising increases the probability of rule-breaking acts more for individuals with higher crime propensity. Hence, structural time use might explain patterns of unstructured socialising, and crime propensity might explain why some are at an increased risk of committing rule-breaking acts during such situations. The present study aims to connect these three aspects and examine: (i) how adolescents tend to structure their time use, (ii) if their structural time use differentially places them in unstructured socialising, and (iii) whether some adolescents during unstructured socialising run an elevated risk of committing rule-breaking acts due to their morality (as part of their crime propensity) while also taking their structural time use into account. Using a sample of 512 adolescents (age 16) in Sweden, time use and morality are analysed using latent class analysis based on space-time budget data and a self-report questionnaire. Multilevel linear probability models are utilised to examine how rule-breaking acts result from an interaction between an individual?s morality and unstructured socialising, also taking structural time use into account. Results show that the likelihood of unstructured socialising in private but not in public is different across identified latent classes. Adolescents, in general, run an elevated risk of rule-breaking acts during unstructured socialising, irrespective of structural time use. In this study, these acts consist mainly of alcohol consumption. However, the risk is higher for adolescents with lower morality. Adolescents? time use may account for a general pattern of delinquency, but accounting for rule-breaking acts requires knowledge of the interaction between person and setting.